The steel industry in Japan a comparison with Britain - Hasegawa, Harukiyo (Sheffield Centre for Japanese Studies/Routledge series, 1996)
The Japanese steel industry has experienced both boom and recession over the past 30 years and is now in real decline. This study analyzes the economic, technical and political changes paying particular attention to the impact of modern technology upon employees within the industry. It introduces an important conceptual tool for comparative study: "convergence". Challenging the simplistic notion of "leader" and "follower" industries, the text utilises this concept to investigate whether the steel industry, and by extension other manufacturing industries, can survive in mature economies.